RETRACTED: Knockdown of Long Non-Coding RNA KCNQ1OT1 Restrained Glioma Cells’ Malignancy by Activating miR-370/CCNE2 Axis - Gong, Wei; Zheng, Jian; Liu, Xiaobai; Liu, Yunhui; Guo, Junqing; Gao, Yana; Tao, Wei; Chen, Jiajia; Li, Zhiqing; Ma, Jun; Xue, Yixue (Frontiers in Cellular Neuroscience, 2017)
Accumulating evidence has highlighted the potential role of long non-coding RNAs (lncRNAs) as biomarkers and therapeutic targets in solid tumors. Here, we elucidated the function and possible molecular mechanisms of lncRNA KCNQ1OT1 in human glioma U87 and U251 cells. Quantitative RT-PCR demonstrated that KCNQ1OT1 expression was up-regulated in glioma tissues and cells. Knockdown of KCNQ1OT1 exerted tumor-suppressive function in glioma cells. Moreover, a binding region was confirmed between KCNQ1OT1 and miR-370 by dual-luciferase assays. Quantitative real-time PCR showed that miR-370 was down-regulated in human glioma tissues and cells. In addition, restoration of miR-370 exerted tumor-suppressive function via inhibiting cell proliferation, migration and invasion, while promoting the apoptosis of human glioma cells. Knockdown of KCNQ1OT1 decreased the expression level of CCNE2 by binding to miR-370. Further, miR-370 bound to CCNE2 3′UTR region and decreased the expression of CCNE2. These results provided a comprehensive analysis of KCNQ1OT1-miR-370-CCNE2 axis in human glioma cells and might provide a novel strategy for glioma treatment.